Detailed void characterisation by X-ray computed tomography of material extrusion 3D printed carbon fibre/PEEK. (15th March 2023) - Sommacal, S.; Matschinski, A.; Holmes, J.; Drechsler, K.; Compston, P.
Graphical abstract: Highlights: Micro-CT to acquire high resolution images of ME (FFF) 3D printed CF/PEEK material. First comparative quantitative porosity study of printed samples & parent filaments. Compilation of geometric characteristics for over one million voids. ME (FFF) printing effect on sample microstructure qualitatively & quantitatively assessed. Abstract: Material extrusion (ME) is one of the most popular techniques for 3D printing. However, despite offering almost unlimited flexibility in the design and choice of material of the printed components, it is yet to be widely adopted in the industry. Mechanical properties of printed parts are usually below expectations and this can be caused by the presence of voids, the most commonly encountered structural defect. Besides quantity, void type, shape, size, and their location, density and distribution within the microstructure can affect the material's mechanical properties. Detailed knowledge of void geometric characteristics is also crucial for modelling and simulation, and there is a need for comprehensive experimental derived void databases. In this work, X-ray micro-computed tomography has been utilised to image two samples printed by ME and their respective parent feedstock filaments. Voids have been identified, quantified, mapped in 3D, then individually labelled, and their key geometrical characteristics extracted and analysed. Furthermore, the effects of the printing process on voids' geometry and distribution have been qualitatively and quantitatively assessed.